Peran Entrepreneurial Orientation dan Learning Capability: Persepektif Resource Based Heory - Hayati Nupus; Faqih Nabhan (J-MAS (Jurnal Manajemen dan Sains), 2023)
This research begins with gap research on the influence of the introduction of entrepreneurial orientation on company performance based on the Resource-based theory (RBT). This study analyzes the effect of entrepreneurial orientation assistance and learning ability on company performance which is mediated by the competitive advantage of halal food SMEs in the city of Salatiga. The results of multiple linear regression of 112 respondents stated that entrepreneurial orientation, company performance had a significant positive effect on company performance, and competitive advantage was able to mediate the effect of entrepreneurial orientation and learning ability on company performance.